2017
DOI: 10.3837/tiis.2017.12.021
|View full text |Cite
|
Sign up to set email alerts
|

EAR: Enhanced Augmented Reality System for Sports Entertainment Applications

Abstract: Augmented Reality (AR) overlays virtual information on real world data, such as displaying useful information on videos/images of a scene. This paper presents an Enhanced AR (EAR) system that displays useful statistical players' information on captured images of a sports game. We focus on the situation where the input image is degraded by strong sunlight. Proposed EAR system consists of an image enhancement technique to improve the accuracy of subsequent player and face detection. The image enhancement is foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…For example, S. Lee, Ahn, Hwang, and Kim (2011) implemented a vision-based AR system that displayed supplementary information about the position of each player during the baseball game. Such algorithms could identify players during matches and address the comments to them during debrief sessions (Mahmood et al, 2017). Figure 5: Adding information using virtual elements might improve viewers' experience.…”
Section: Interacting With Sports Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, S. Lee, Ahn, Hwang, and Kim (2011) implemented a vision-based AR system that displayed supplementary information about the position of each player during the baseball game. Such algorithms could identify players during matches and address the comments to them during debrief sessions (Mahmood et al, 2017). Figure 5: Adding information using virtual elements might improve viewers' experience.…”
Section: Interacting With Sports Eventsmentioning
confidence: 99%
“…However, Kinect's limited application for complex movements, such as standing techniques in Judo stems from its inability to see the body parts in the optical shade (Sieluzycki et al, 2016). This limitation can be resolved with machine learning and computer vision algorithms that could be used to improve the accuracy of such systems (Mahmood et al, 2017). In any case, the accuracy of AR systems must be tested since the human visual system can detect slight shifts between the virtual image and the targeted actual display location.…”
Section: Systems Technical Limitationsmentioning
confidence: 99%
“…It has been shown that robotic cameramen facilitate more precise and advanced interaction with virtual elements, and through zooming and multiple angle views, improve the performance of AR broadcasting in all sorts of environments. An enhanced AR system displays statistical players' information on captured images of a sports game [41]. It is an image enhancement technique based on an algorithm that implements multi-scale retinex.…”
Section: Ar In Entertainmentmentioning
confidence: 99%
“…RGB is most natural colour space but more sensitive to change in lights [18]. Owing to more nearest to human colour perception, hue, saturation, and value (HSV) or hue, intensity, and saturation [19] are more popular. The colour space is also less affected by illumination, but its computational cost is high.…”
Section: Detectionmentioning
confidence: 99%